PENGARUH Trichoderma sp. TERHADAP PERTUMBUHAN VEGETATIF TANAMAN KRISAN (Chrysanthemum morifolium R.) VAR. JAYANI - Marsela Deana Ratu; Bertje R.A. Sumayku; Ventje Pangemanan; Jantje Pongoh; Antje Grace Tulungen; Yefta Pamandungan (EUGENIA, 2024)
Chrysanthemum (Chrysanthemum morifolium) is the most popular plant in Indonesia, because chrysanthemum flowers have their own advantages in terms of the beauty of their flower colors. The problem with chrysanthemum shoot cuttings is that the roots are not dense enough so that the chrysanthemum plant cannot grow upright. This research aims to determine the effect of Trichoderma sp. on vegetative growth of chrysanthemum plants. This research was carried out for 5 weeks, starting from July to August 2023 at the Green House of the Seed, Nursery and Agrotourism Center, Tomohon City. The method that will be used in this research is a Completely Randomized Design (CRD), with 5 treatments: P0 = No Trichoderma sp. (Control), P1 = Thricoderma sp. 25 gr/l, P2 = Thricoderma sp. 50 gr/l, P3 = Thricoderma sp. 75 gr/l, P4 = Thricoderma sp. 100 gr/l. All treatments were repeated 5 times so that there were 25 units. The data obtained based on observations in this research will be analyzed using Analysis of Variance (ANOVA). The variables observed were: number of leaves, plant height, number of roots, root length. The results of the study showed that the use of Trichoderma was not significantly different from the variables number of leaves, plant height and root length. Giving trichoderma only had a significant effect on the number of roots (giving 50g trichoderma/liter of water). Keywords: trichoderma sp., chrysanthemum cuttings, growth, results